The temporary as the future: Ready‐to‐use therapeutic food and nutraceuticals in South Africa - Pentecost, M; Cousins, T (Wiley, 2018)
The reconfiguration of food as a pharmaceutical in biomedical regimes has been considered by scholars along two axes: (1) food supplementation as humanitarian intervention, based on a specific value of life and delivered in ‘crisis’ situations with a short temporal horizon; (2) food supplementation as commodity, marketed as enhancing ‘wellness’ or potential, based on notions of risk in broad temporal frames. We consider nutraceuticals and ready‐to‐use‐therapeutic foods as they are deployed by state and commercial actors in South Africa in relation to two key figures: the pregnant woman and the HIV‐positive population. These biopolitical expressions of post‐apartheid regimes of knowledge, care and governance reveal how state distribution and the corporate marketing of supplements employ a future‐oriented logic that appeals to notions of power, energy and potential. Therapeutic foods in this context are thus not merely humanitarian technologies that reconfigure crisis as a chronic condition – the temporary becoming permanent – but are premised on new potentialities, in which the temporary may (re)shape the future.